The Aesthetic Taste Representation of Coastal Community (Harmonia: Journal of Arts Research and Education, 2020)
Aesthetic tastes of a person to an art form are determined by the knowledge and experience that comes from the culture of the community. In this regard, this study aims to determine the aesthetic tastes of coastal communities as reflected in the collaborative packaging of the traditional art of Barong Ngesti Wargo Budoyo. The method used was a qualitative research method with data collection techniques, observation, interviews and documentation, then the data were analyzed based on interactive data analysis which the flow were data reduction, data presentation, drawing conclusions and verification. The results showed that the collaborative packaging of the traditional art of Barong Ngesti Wargo Budoyo received tremendous appreciation from coastal communities, it was shown that every performance of this art was always full of audiences of all ages. The audience in the show as if there is no distance, the audience can also interact with players. The phenomenon that occurs in collaborative performances of traditional arts, indicates that the collaborative packaging of traditional arts represents the packaging of shows that suits the aesthetic tastes of coastal communities.Â  Community tastes based on their characteristics can be categorized into popular taste.